Teaching the US 2018 midterm elections: a survey of secondary social studies teachers. Issue 4 (4th July 2022) - Stoddard, Jeremy; Fitchett, Paul; Hess, Diana
ABSTRACT: The goal of this study was to identify teacher-reported practices related to teaching the 2018 US Midterm Elections and contemporary social and policy issues. In particular, we sought to identify factors that helped explain why teachers were or were not engaging students in the midterm elections and related contemporary issues and what contextual factors may influence their teaching of these contemporary events. We also examined how the teachers' political views and those of the school community, personal political engagement and engagement with current events were associated with teaching the midterms. Respondents to our online survey, conducted using a regionally stratified sample in late 2018, include 813 US secondary social studies teachers from 48 states. We found that teachers who identified shared goals with colleagues and administrators and who reported having autonomy over their curriculum and teaching said they engaged students in the election and issues regardless of the political context. We also found that teachers in more politically competitive states reported developing skills, norms and classroom contexts conducive for engaging in controversial issues. These findings are important given the rise in populism, partisanship and social stratification in the US and globally.